2022
DOI: 10.3390/ijms231911757
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4, CXCR5 and CD44 May Be Involved in Homing of Lymphoma Cells into the Eye in a Patient Derived Xenograft Homing Mouse Model for Primary Vitreoretinal Lymphoma

Abstract: Background: Primary vitreoretinal lymphoma (PVRL), a rare malignancy of the eye, is strongly related to primary central nervous system lymphoma (PCNSL). We hypothesized that lymphoma cells disseminate to the CNS and eye tissue via distinct homing receptors. The objective of this study was to test expression of CXCR4, CXCR5, CXCR7 and CD44 homing receptors on CD20 positive B-lymphoma cells on enucleated eyes using a PCNSL xenograft mouse model. Methods: We used indirect immunofluorescence double staining for CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Thus, we explored the regulation of CD44 expression by MyD88 L265P in more detail. Many previous studies reported an important functional role of CD44 in various types of cancer [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and increased CD44 expression has also been observed in lymphoma [ 55 , 56 , 57 , 58 , 59 , 60 ]. Since we identified CD44 as a prominent downstream target of MyD88 L265P oncogenic NF-κB signaling, we wondered whether CD44 might serve as a cell surface marker of MyD88 L265P -dependent DLBCL lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we explored the regulation of CD44 expression by MyD88 L265P in more detail. Many previous studies reported an important functional role of CD44 in various types of cancer [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and increased CD44 expression has also been observed in lymphoma [ 55 , 56 , 57 , 58 , 59 , 60 ]. Since we identified CD44 as a prominent downstream target of MyD88 L265P oncogenic NF-κB signaling, we wondered whether CD44 might serve as a cell surface marker of MyD88 L265P -dependent DLBCL lymphoma.…”
Section: Resultsmentioning
confidence: 99%
“…PCNSL xenografted mice. PVRL lymphoma cells in this model expressed chemokine receptors CXCR4 and CXCR5 as well as CD44 [45].…”
Section: Discussionmentioning
confidence: 99%